Use of technologies in thyroid surgery: Latin American Thyroid Society Surgical Affairs Committee Expert Opinion. Part 1 - Alvaro Sanabria; Jose Luis Novelli; Erivelto Volpi; Ana Voogd; Santiago Zund; Luiz Paulo Kowalski; Juan Pablo Dueñas (Archives of Endocrinology and Metabolism)
ABSTRACT Thyroidectomyis the most frequent endocrine surgical treatment for problems such as goiter, thyroid cancer, and Graves’ disease. The global incidence of goiter ranges from 5%-20%, with a notably high frequency in less wealthy countries, and the incidence of thyroid cancer is on the rise due to the greater use of diagnostic imaging. Despite medical options, surgery remains essential. Surgical advancements such as blood vessel sealing technology, intraoperative laryngeal nerve neuromonitoring (IONM), remote access surgery, and parathyroid fluorescence have transformed thyroid surgery. Vessel sealing technologies reduce operative time and blood loss, whereas IONM preserves the laryngeal nerves. Remote access surgery, which includes a variety of techniques, produces results similar to those of open thyroidectomy with a longer operative time. Fluorescence enhances parathyroid detection and lowers the risk of temporary hypoparathyroidism. Economic studies reveal cost discrepancies, with advantages particularly visible in health care systems that depend on surgical time. While these advancements promise better patient outcomes, their accessibility and cost-effectiveness remain issues, particularly in Latin America. Recognizing these concerns, the Latin American Thyroid Society’s Surgical Affairs Committee conducted an extensive review of emerging thyroid surgery technologies to guarantee their proper use in the area.